A criança surda na Educação Infantil: o desenvolvimento de linguagem na perspectiva do professor - Pinto, Milena Maria (Universidade Federal de São Carlos, 2021)
The diversity in the current school context, considering the target audience of Special Education, brought relevant changes to education, especially regarding the inclusive proposal, resulting in different professional practices and teaching models. Concerning the deaf, education for this public has as main parameters the linguistic and cultural differences, which should be prioritized in the learning process through bilingual education. In this context, this work aims to investigate, understand and problematize how the child language development process takes place from the teacher. This is qualitative research, whose instrument for data collection was the use of an online questionnaire - via Google Forms, with open and multiple choice questions. The participants are 15 hearing teachers who work or have worked in Early Childhood Education classrooms with the presence of one or more deaf students in public schools in the state of São Paulo in the last four years. The questions seek to understand specific points about the teacher's perspective regarding the language of deaf children, regardless of the proposal and school team. The discussions and results were elaborated from the responses to the form and the data were organized in thematic axes, according to the objectives of this research. The data analyses are anchored in the assumptions of the historical-cultural approach and indicate the impacts of social relations on the formation of the deaf subject, highlight the conceptions of teachers; language and experiences in the educational context before contact with Libras, generating reflections on inclusive and bilingual school proposals. It is expected, from this research, to contribute to studies in the area of Special Education and deaf education, especially regarding child development in this educational stage.
Deaf children in Early Childhood Education: language development from the teacher's perspective
Keywords: Educação Infantil; Desenvolvimento linguístico; Crianças surdas; Bilinguismo; Inclusão; Perspectiva Histórico-cultural; Educadores; Early childhood education; Linguistic Development; Deaf children; Bilingualism; Inclusion; Historical-cultural perspective; Educators; CIENCIAS HUMANAS::EDUCACAO; CIENCIAS HUMANAS::EDUCACAO::TOPICOS ESPECIFICOS DE EDUCACAO